The role of labor in the development of rural areas - Abayev, А.А. (BUKETOV BUSINESS REVIEW, 2017)
The paper discusses the features of the formation problem of the labor force in rural areas are discussed in this paper. The author defined the labor as the working population engaged in labor activities. The labor force in rural areas is presented in the form of permanent, seasonal and other categories of workers. The author analyzed the structure of the economically active rural population of the Republic of Kazakhstan, as well as their employment for the years 2011-2015. There is a decrease in the economically active rural population of the Republic of Kazakhstan, which are mainly related to the reduction of birth rate, natural population loss, retirement from the rural areas, and low attractiveness of the prospect of living and working in rural areas for young people. The article describes the rural unemployed population for 2015 by level of education. The author notes that the existing vacancies in the countryside are not in demand because of the low level of wages in comparison with other sectors of the economy. There is the structure of the employed rural population in the context of gender policy. Recommendations to further improve of the employment of rural areas are given.